2022
DOI: 10.1039/d1cc05148b
|View full text |Cite
|
Sign up to set email alerts
|

Osmium(vi) nitride triggers mitochondria-induced oncosis and apoptosis

Abstract: We report a new osmium(VI) nitrido complex bearing a nonplanar tetradentate ligand with potent anticancer activity. It causes mitochondrial damage, which induces liver cancer cell death via oncosis and apoptosis....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In 2018, a family of cyclometalated iridium(III) compounds bearing benzothiazole ligands were reported for the first time as inducers of a novel, non-apoptotic type of cell death known as oncosis [7]. Recently, an osmium(IV) nitride compound was also found to elicit oncosis in cancer cells [8]. Oncosis (from Greek ónkos, meaning "swelling") refers to a cell death process related to energy depletion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a family of cyclometalated iridium(III) compounds bearing benzothiazole ligands were reported for the first time as inducers of a novel, non-apoptotic type of cell death known as oncosis [7]. Recently, an osmium(IV) nitride compound was also found to elicit oncosis in cancer cells [8]. Oncosis (from Greek ónkos, meaning "swelling") refers to a cell death process related to energy depletion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular reactive oxygen species (ROS) oxidative stress can induce cell apoptosis. 18,19 We determined the ROS levels in 6-treated cells by inverted fluorescence microscope and flow cytometry with 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) stained. In the presence of cellular ROS, DCFH-DA can be converted to DCF, which displays green fluorescence.…”
Section: Dalton Transactions Accepted Manuscriptmentioning
confidence: 99%
“…The clinical success of platinum-based anticancer drugs such as cisplatin, carboplatin, and oxaliplatin has stimulated extensive investigations into new metallodrugs with improved pharmacological properties, which may reduce side effects, such as kidney toxicity and nausea, and overcome drug resistance [ 2 , 3 , 4 ]. Recently, other metal-based compounds with potential anti-cancer properties have been reported [ 5 , 6 ]. Ruthenium compounds are a potential alternative to platinum-based drugs owing to their chemical and pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a new osmium(VI) nitrido complex bearing a nonplanar tetradentate ligand with potent anticancer activity. It causes mitochondrial damage and induces liver cancer cell bimodal death via oncosis and apoptosis [ 5 ]. Lippard et al found that the cellular response evoked by anti-proliferating osmium(VI) nitrido compounds with bidentate lipophilic N,N-chelating ligands could be tuned by subtle ligand modifications [ 13 ].…”
Section: Introductionmentioning
confidence: 99%